General chemistry 2 - Lontoc, Betty M.; Paderna, Edwehna Elinore S.; Ilao, Luciana V. (Sampaloc Manila : Rex Book Store, Inc., 2022)
"General Chemistry 2 discusses more the properties and the changes in matter, together with the changes in energy during chemical reactions. Each topic is presented through a holistic approach with emphasis on contextual applications. This worktext aims to satisfy the requirements of the Science component of the K to 12 curriculum. The topics are presented with contextualized examples that are familiar to students to help them understand the principles easily, The discussions also come with a variety of examples, class activities, and exercises as supplements to aid the students' understanding of the chemistry principles and concepts."
Includes bibliographical references.
English text.
Keywords: Chemistry